Redundant functions of I-BAR family members, IRSp53 and IRTKS, are essential for embryonic development - Chou, Ai Mei (Sci Rep, 2017)
The insulin receptor substrate of 53 kDa, IRSp53, is an adaptor protein that works with activated GTPases, Cdc42 and Rac, to modulate actin dynamics and generate membrane protrusions in response to cell signaling. Adult mice that lack IRSp53 fail to regulate synaptic plasticity and exhibit hippocampus-associated learning deficiencies. Here, we show that 60% of IRSp53 null embryos die at mid to late gestation, indicating a vital IRSp53 function in embryonic development. We find that IRSp53 KO embryos displayed pleiotropic phenotypes such as developmental delay, oligodactyly and subcutaneous edema, and died of severely impaired cardiac and placental development. We further show that double knockout of IRSp53 and its closest family member, IRTKS, resulted in exacerbated placental abnormalities, particularly in spongiotrophoblast differentiation and development, giving rise to complete embryonic lethality. Hence, our findings demonstrate a hitherto under-appreciated IRSp53 function in embryonic development, and further establish an essential genetic interaction between IRSp53 and IRTKS in placental formation.